2011
DOI: 10.1152/ajpheart.00277.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine administration in a mouse model of familial hypertrophic cardiomyopathy, α-tropomyosin D175N

Abstract: Gaffin RD, Chowdhury SA, Alves MS, Dias FA, Ribeiro CT, Fogaca RT, Wieczorek DF, Wolska BM. Effects of nicotine administration in a mouse model of familial hypertrophic cardiomyopathy, ␣-tropomyosin D175N. Am J Physiol Heart Circ Physiol 301: H1646-H1655, 2011. First published July 8, 2011 doi:10.1152/ajpheart.00277.2010.-The effects of nicotine (NIC) on normal hearts are fairly well established, yet its effects on hearts displaying familial hypertrophic cardiomyopathy have not been tested. We studied both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Echocardiography. Echocardiography was performed on anesthetized mice (3.5% isoflurane with 100% oxygen induction with 1.5% isoflurane in 100% oxygen maintenance) using a VisualSonics' Vevo 2100 ultrasound machine and MS550D (40 MHz) transducer as previously reported (2,28). Transthoracic B-mode, M-mode, pulsed Doppler, and tissue Doppler images were obtained from the parasternal short-axis view (systolic and morphology parameters) and the apical view (diastolic parameters).…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography. Echocardiography was performed on anesthetized mice (3.5% isoflurane with 100% oxygen induction with 1.5% isoflurane in 100% oxygen maintenance) using a VisualSonics' Vevo 2100 ultrasound machine and MS550D (40 MHz) transducer as previously reported (2,28). Transthoracic B-mode, M-mode, pulsed Doppler, and tissue Doppler images were obtained from the parasternal short-axis view (systolic and morphology parameters) and the apical view (diastolic parameters).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of persistent pregnant smokers, the smokers reported higher prenatal stress and depression than non-persistent smokers or non-smokers (Eiden et al, 2011 ). Women were also found to be more vulnerable to the depressive symptoms of nicotine withdrawal (Gaffin et al, 2011 ). Acutely, nicotine has been found to be more anxiolytic in female than in male rats (Harrod et al, 2004 ), corroborating human studies which also document that females are more susceptible to the effects of nicotine on anxiety (Pogun and Yararbas, 2009 ).…”
Section: Brain Effects Of Nicotine: Similarities and Differences Withmentioning
confidence: 99%